2015
DOI: 10.1177/0731684415584784
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and degradation properties of successive alkali treated completely biodegradable sisal fiber reinforced poly lactic acid composites

Abstract: The natural fiber reinforced biodegradable polymer composites were prepared with short sisal fiber as reinforcement in poly lactic acid (PLA) matrix. The sisal fiber is treated with 10% NaOH followed by H 2 O 2 . The composites were prepared with untreated and treated short sisal fibers at different weight proportions up to 25% in PLA matrix and investigated for mechanical and degradation properties. The results showed that the composite with treated fiber at 20% fiber loading has shown 30% and 8% higher tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…As can be noted from the SEM images, the treated Napier fibers showed a rougher outer surface than the untreated fibers. This was due to the treatment which removed the impurities, lignin, oil, and waxy substances that cover the external fiber surface, which led to fibrillation, creating a rougher topography and thus enabling them to bind strongly with the epoxy resin . As a result, the fiber/epoxy adhesion was enhanced after the chemical treatment.…”
Section: Resultsmentioning
confidence: 99%
“…As can be noted from the SEM images, the treated Napier fibers showed a rougher outer surface than the untreated fibers. This was due to the treatment which removed the impurities, lignin, oil, and waxy substances that cover the external fiber surface, which led to fibrillation, creating a rougher topography and thus enabling them to bind strongly with the epoxy resin . As a result, the fiber/epoxy adhesion was enhanced after the chemical treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that erosion resistance of treated samples is 20%-30% lower than untreated samples for 60°impact angle. Chemical treatment of natural fibers intended to improve the adhesion with polymer matrices were reported by numerous researchers [80][81][82][83][84][85][86][87][88]. However they had used different chemicals in their studies.…”
Section: Effect Of Fiber Treatmentmentioning
confidence: 99%
“…; Rajesh et al . ; Xia et al . ), there are limited reports on the combination of bio‐based polymers with natural fibers and AM agents in packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies that suggest PLA is a suitable matrix for the incorporation of natural fibers in biocomposites (Awal et al 2015;Rajesh et al 2015;Xia et al 2015), there are limited reports on the combination of biobased polymers with natural fibers and AM agents in packaging applications. In one example, the inhibition of E. coli in liquid media by PLA/triclosan films a was enhanced when the film was incorporated with 10% w/w wood fibers (Prapruddivongs and Sombatsompop 2012).…”
Section: Introductionmentioning
confidence: 99%